Psychological readiness for return to sport after musculoskeletal injury in volleyball players: a systematic literature review - Rudyanto Rudyanto; Eval Edmizal; Jeki Haryanto (IICET (Indonesian Institute for Counseling, Education and Therapy), 2026)
Volleyball injury can be considered as one of the inherent risks of the game as it is a high-impact jumping sport with the knee, ankle and shoulder being the main parts of the body exposed to the heavy load repeatedly. The period after the physical recovery from injury is also being understood as a psychological issue along with a biomechanical one. Researches on physical recovery have been done extensively but only a few studies have attempted to explore the psychological aspect especially the confidence of an athlete to resume the competition after injury in volleyball populations. This systematic literature review was conducted to gather and analyze the existing evidence on psychological readiness to return to sport following injury among volleyball players and, also, in the larger population of injured athletes who are relevant to volleyball. The review followed the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) paper. Scopus database was the main source of information, and a Boolean strategy was applied to combine terms for volleyball, injury, psychological readiness and return to sport in the title, abstract and keyword fields. The search returned 783 records; after eliminating 11 duplicates, 772 records were screened, 69 full texts were assessed for eligibility, and 10 studies met all inclusion criteria. Four major thematic findings are as follows: psychological readiness is a quantifiable, multi-dimensional factor with confidence and fear of re-injury being the most dominant two elements; readiness has a consistent negative correlation with pain, kinesiophobia and second-injury risk; protective psychological resources such as mental toughness, athletic identity and adaptive achievement goals can influence the recovery trajectory; and criterion-based assessment which is validated is increasingly incorporating psychological along with functional testing. Theoretically, these findings substantiate the biopsychosocial model of the return to sport; practically, they are in support of the regular, sport-specific evaluation of readiness by coaches and rehabilitation teams. We recommend future research to focus on prospective, volleyball-specific cohorts, designs that are longitudinal, and the use of wearable devices combined with psychological assessment to enhance the precision of return-to-sport decision-making.